Implementation of a human vital monitoring system using ad hoc wireless network for smart healthcare - Insom, Poramin; Wongpanitlert, Pakorn; Tipsupa, Jakree; Rakjang, Kritsakorn; Kaemarungsi, Kamol; Watanachaturaporn, Pakorn (My University, 2011)
A human vital monitoring system using Ad Hoc wireless network is implemented to enhance the healthcare service. Issues related to hardware and software implementation including the data packet format are addressed. The system uses a low cost electrocardiogram (ECG) sensor to monitor patient's vital sign. A sensor node, which is held by the patient, transmits the sensor data via an Ad Hoc wireless network to a gateway. The received data is processed and displayed in a form of graph on a monitoring screen. The system allows medical personal to check the status of patient remotely. Too the system is designed such that, if it detects anomaly signs from the patient, the sensor node can report an alarm to the monitoring screeen so that medical personal can assist the patient immediately. The system is developed using a real-time operating system and deployed an Ad Hoc routing protocol to reroute the packet to the gateway automatically. © 2011 IEEE.
Keywords: Ad hoc wireless network; Healthcare; Monitoring system